Teaching And Learning Programs For Autistic Children. - See, Assoc. Prof. Dr., Ching Mey (2005)
The psychologist, Leo Kanner, separated autism from others and coined the term, infantile autism in 1943. The word "autism" comes from the Greek words - "au", which means "self' and "ism", which implies "orientation or state". Autism is then the condition of somebody who is unusually absorbed in himself or herself (Reber, 1985). It is a lifelong disability affecting areas of the brain that control understanding, emotions, speech and gesticulation, and the general ability to interact socially.